Inferioritas dan Superioritas Tokoh dalam Novel Hello Salma Karya Erisca Febriani: Kajian Psikologi Individual Alfred Adler - Fara Dila Silvi Wulandari; Sri Yanuarsih; M. Imron Abadi (FKIP, Universitas Palangka Raya, 2024)
Inferiority and superiority are part of Alfred Adler's concept of individual psychology. The purpose of this study is to understand more deeply about the forms of inferiority in the aspects of feeling (1) insecure, (2) shyness, (3) withdrawing from the environment (withdrawal), forms of superiority in the aspects of (1) defense ego, (2) confident, (3) patient, (4) idealistic, in the novel Hello Salma by Ersica Febriani. The method used is descriptive qualitative. The data were obtained in the form of facts and then analyzed using the Psychology of Literature approach. Collection techniques namely reading notes, literature study, and corpus. Analysis techniques through the preparation stage, collecting theory, selecting, analyzing, drawing conclusions, and preparing reports. The results of the study show the inferiority of the characters in terms of feelings: (1) insecure including pessimism, lack of confidence experienced by Nathan and Salma. (2) Shyness (shyness), a feeling of anxiety about other people's views of her owned by Rebecca, as well as Salma's silent and awkward attitude. (3) Withdrawing from the environment (withdrawal), feeling uncomfortable, insecure in a social environment, often seen alone, was found in Rebcca. Forms of superiority aspect: (1) Ego defense, maintaining self-image as well as trying to accept Nathan's situation. (2) Confidence, belief in one's own abilities, having a strong drive for achievement that Rebecca feels. (3) Patience, keeping the soul from complaining, patiently accepting fate, not giving up easily that Salma encountered. (4) Idealistic, the idea that becomes the principle of life in accordance with the foundation that is considered perfect by the character Salma.